Photophysical and photochemical study on novel axially chalcone substituted silicon (IV) phthalocyanines - Kahriman, Nuran; Unver, Yasemin; Akcay, Hakki Turker; Gulmez, Asuman Dakoglu; Durmuş, Mahmut; Degirmencioglu, Ismail (Elsevier, 2020)
The novel axially chalcone bearing furan or thiphene groups substituted silicon (IV) phthalocyanine complexes were synthesized in this study. These novel phthalocyanines were characterized by general spectroscopic methods such as FT-IR, 1(H) NMR, UV-Vis, and MALDI-TOF. The aggregation behaviours of the synthesized phthalocyanines were investigated in different solvents and at different concentrations by UV-Vis spectroscopy. The aggregation behavior of the synthesized phthalocyanines were studied at different concentration and different solvents and it was observed chloroform and tetrahydrofuran solutions of furan substituted phthalocyanine (3a) show J-type aggregation as unusual. The photophysical and photochemical properties of the synthesized silicon(IV) phthalocyanine complexes were investigated in dimethylformamide (DMF). It was observed that although both of fluorescent and singlet oxygen quantum yields of the compounds were similar, thiophene substituted phthalocyanine Si(IV) complex show higher quantum yield (3b) than that of furan substituted (3a). (C) 2019 Published by Elsevier B.V.
Keywords: Phthalocyanine; Fluorescence; Singlet oxygen; Aggregation